Linear rotor in an ideal Bose gas near the threshold for binding - Dome, Tibor; Volosniev, Artem; Ghazaryan, Areg; Safari, Laleh; Schmidt, Richard; Lemeshko, Mikhail (Physical review, 2024)
We study a linear rotor in a bosonic bath within the angulon formalism. Our focus is on systems where isotropic or anisotropic impurity-boson interactions support a shallow bound state. To study the fate of the angulon in the vicinity of bound-state formation, we formulate a beyond-linear-coupling angulon Hamiltonian. First, we use it to study attractive, spherically symmetric impurity-boson interactions for which the linear rotor can be mapped onto a static impurity. The well-known polaron formalism provides an adequate description in this limit. Second, we consider anisotropic potentials, and show that the presence of a shallow bound state with pronounced anisotropic character leads to a many-body instability that washes out the angulon dynamics.
Online veröffentlicht: 5. Januar 2024
Gesehen am 30.07.2024